Epidemiologia e aspectos clínicos perioperatórios de tumores encefálicos: análise de 627 casos consecutivos operados no Hospital Geral de Fortaleza - Maia, Rafael Costa Lima (2024)
Introduction: With high morbidity and mortality, brain tumors still represent a field of study with various peculiarities to be discussed. There are no epidemiological studies related to the Northeast of Brazil. Objectives: To understand the epidemiology of brain tumors at the reference hospital in the state of Ceará (Brazil) and the relationship of 14 perioperative clinical aspects that change the approach to patients. Method: A retrospective quantitative and qualitative cross-sectional study. Cases of primary and secondary brain tumors, submitted between January 2014 and December 2016 to microsurgery, neuroendoscopy, and stereotaxis-guided biopsy, were analyzed. The statistical significance level used was p<0.05 (2-sided), and all analyses were performed using SPSS software for Windows (version 20.0) and GraphPad Prism (version 6.0). Results: A total of 627 patients were included, with an average patient age of 48.9 years, 52.8% of whom were male. The most common tumors were gliomas (28.3%), meningiomas (23.1%), pituitary adenomas (19.6%), and brain metastases (12.3%). There was a significant relationship (p < 0.05) with the presence of hydrocephalus and perioperative aspects: surgery duration, ICU stay duration, and total hospitalization time. These same aspects were also influenced (i.e., also had statistically significant associations) by whether or not preoperative embolization was performed and by early extubation. The type of hospitalization (whether elective or through the emergency department) impacted the duration of surgery and also influenced the total hospitalization time - this aspect was also related to having previously undergone neurosurgery. The occurrence of the need (yes or no) for emergency surgery was higher in younger patients. Conclusion: Statistically significant relationships between perioperative aspects and epidemiological peculiarities were pointed out.